Special Educators’ Preference in Assessing Students With Special Needs Amidst Pandemic - Cortes, Venus M; Vano, Sueila Anne S; Simbajon, Keziah; Villaflor, Audrey Ann; Lisondra, Patricia Joy; Mayot, Jenny Mae (Technium Education and Humanities, 2022)
The study aimed to perceive the preferred assessment tools utilized by special education teachers with the new learning modalities in correspondence to the pandemic started to burgeon. It employed Braun and Clarke’s Thematic Analysis which the researchers used to evaluate and analyze the qualitative data in the study. Moreover, the study focused on the alternative assessment, which branches out into two types: Performance-based and authentic. The investigation of the study entails thematic analysis, which divulges three themes: "Current Assessment used in the new learning modality," "Challenges encountered by the special education teachers," and "Assessment recommendation." The inferred extracted narrative of the five special education teachers as participants counted as a conception of experiences. (1) Special education teachers’ preferred assessment caters to specific needs of the students through performance-based and authentic assessments (2) Special Education teachers’ preferred assessment anchors specific modification in assessment tools through alternative assessments (3) Special Education teachers’ preferred assessment encompasses available learning resources both for students and teachers. Based on the three conceptions, the following preference surfaced as promulgated: Special Educators’ discretion in assessing students with special needs in an online and offline learning mode. The study aimed to perceive the preferred assessment tools utilized by special education teachers with the new learning modalities in correspondence to the pandemic started to burgeon. It employed Braun and Clarke’s Thematic Analysis which the researchers used to evaluate and analyze the qualitative data in the study. Moreover, the study focused on the alternative assessment, which branches out into two types: Performance-based and authentic. The investigation of the study entails thematic analysis, which divulges three themes: "Current Assessment used in the new learning modality," "Challenges encountered by the special education teachers," and "Assessment recommendation." The inferred extracted narrative of the five special education teachers as participants counted as a conception of experiences. (1) Special education teachers’ preferred assessment caters to specific needs of the students through performance-based and authentic assessments (2) Special Education teachers’ preferred assessment anchors specific modification in assessment tools through alternative assessments (3) Special Education teachers’ preferred assessment encompasses available learning resources both for students and teachers. Based on the three conceptions, the following preference surfaced as promulgated: Special Educators’ discretion in assessing students with special needs in an online and offline learning mode.